An evaluation of the role of the Philippine Training Centers for Rural Development (PTC-RD) in agricultural extension in the highlands of Region I, Philippines - Delson, Maria Luz Galera; Demaine, Harvey; Weber, Karl E.; Setty, E. Desingu; US-ASEAN Fellowship (Bangkok : Asian Institute of Technology, 1986)
The role of the Philippine Training Centers for (PTC-RD) in agricultural extension in the highlands evaluated after gathering information from trainees, extension workers in the area. Rural Development of Region I was non-trainees, and The major findings show that trainees are different from non-trainees in terms of selected socio-economic characteristics which are educational attainment, area of farms, and presence of other sources of income; that the envisaged function of trainees as farmer-leaders was not carried out; that the agricultural extension workers operating within the area have very little impact on farmers' practices; and that the different rural development-oriented agencies have very limited collab oration among each other as well as with the PTC-RD . Therefore, the major objective of the PTC-RD embodied in its role to "speed up and facilitate agricultural and rural development through an efficient and effective program for the development, distribution and utilization of applicable technologies by the extension workers of all development agencies and institutions within the government and by all Filipino farmers'' is yet to be achieved in the highlands of Region I .
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1986
Keywords: Agricultural extension work -- Philippines